2013
DOI: 10.1186/2228-5326-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy-based study on the interaction between gold nanoparticle and poly(vinylpyrrolidone) molecules in a non-hydrocolloid

Abstract: The study of the interaction between poly(vinylpyrrolidone) (PVP) and gold (Au) nanoparticles (NPs) in a colloid is of special interest for possible applications in the field of catalysis, biosensing, and biomedicine. A strong optical absorption arising from Au NPs at 532 nm in Au-PVP colloids is ascribed to surface plasmon resonance. The X-ray photoelectron spectroscopic results confirm reduction of the Au 3+ ion to Au 0 . A noticeable decrease in the binding energies of the Au4f doublet peak of the Au NP wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 45 publications
(132 reference statements)
5
36
0
Order By: Relevance
“…2 can be explained by assuming that a molecule of IPA is absorbed on the surface of ZnO and then interacts with the surface of the grain via O atoms. It is interesting that the similar conclusion can be drawn from the data describing the synthesis of gold and silver nanoparticles passivated by PVP [44][45][46][47].…”
Section: Ft-ir Spectrasupporting
confidence: 60%
“…2 can be explained by assuming that a molecule of IPA is absorbed on the surface of ZnO and then interacts with the surface of the grain via O atoms. It is interesting that the similar conclusion can be drawn from the data describing the synthesis of gold and silver nanoparticles passivated by PVP [44][45][46][47].…”
Section: Ft-ir Spectrasupporting
confidence: 60%
“…Disappearance of C-H bending vibration of heterocycle ring of MB in presence of oxide NPs also suggests that surface interaction arises between these two entities. In an experiment, Behera and Ram [25] have ascribed a small red shift of 5 cm -1 in the C=O stretching vibration in presence of Au NPs to a weak interaction between poly(vinyl pyrrolidone) polymer and Au surface via the O-atom of the pyrrolidone ring.…”
Section: Resultsmentioning
confidence: 99%
“…Further we studied PL quenching of MB molecules in presence of an oxide quencher using the well-known SternVolmer equation [25,34] which can be written as:…”
Section: Zeta Potential and Xps Studymentioning
confidence: 99%
“…A weak coordinative bond between oxygen atoms in carbonyl group of PVP and metallic Au atoms is the likely cause for the interaction [52][53][54]. Behera et al [49,55] and several others [52,54,56] reported a small shift of C=O stretching vibrations when Au NPs are stabilized by PVP. Earlier reports based on other noble metal NPs such as silver (Ag) and palladium (Pd) account for this carbonyl group shift.…”
Section: Optical and Structural Studiesmentioning
confidence: 99%